SPECIFIC FEATURES OF PEEP ADJUSTMENT IN THE PATIENTS WITH ACUTE RESPIRATORY DISTRESS SYNDROME AND INTRACRANIAL HYPERTENSION - A. V. Oshorov; A. A. Polupan; A. S. Busankin; N. Yu. Tarasova (Вестник анестезиологии и реаниматологии, 2018)
The literature review describes current approaches to management of patients with acute cerebral lesions and intracranial hypertension, complicated by acute respiratory distress syndrome (ARDS). It presents the stages of ventilation strategy evolution in patients with ARDS. The effect of the increase in intrathoracic pressure on system hemodynamics parameters during artificial pulmonary ventilation (APV) is demonstrated. The data on changes in venous return and arterial pressure are presented. The review describes the current understanding of the correlation between pulmonary mechanics and central hemodynamics and effect of these factors on cerebral hemodynamics. The brief description of intracranial tension and cerebral compliance is given. The publication presents the results of up-to-date studies on specific parameters of PEEP optimization in the patients with concurrent acute cerebral lesions, intracranial hypertension, and development of ARDS. Numerous studies were devoted to optimization of APV in case of ARDS, but currently one can not unambiguously conclude about the safe level of PEEP if there is intracranial hypertension. The authors of the article agree with the opinion that more prospective randomized studies are needed and advanced multi-parameter cerebral monitoring is required in case of concurrent pulmonary and cerebral disorders.